The Influence of Work Motivation and Loyalty on ASN Performance with Work Discipline as an Interverning Variable in ASN Rumkit Kindergarten II Iskandar Muda - Syahputra, Andi; Nizamuddin, Nizamuddin (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Human resources (HR) are a very important factor that cannot be separated from an organization, whether institutional or company. HR is also the key that determines the company's development. In essence, HR is in the form of humans who are employed in an organization as movers, thinkers and planners to achieve the organization's goals. The location of the research was carried out at Rumkit Tk II Iskandar Muda, the population of this study was 226 and the sample after being broken down using the Slovin formula was 144. The results of this research are as follows: Work Discipline has been a positive and significant effect on ASN Performance with an original sample value of 0.527 and p value 0.000. Loyalty has a positive and significant effect on Work Discipline with an original sample value of 0.599 and ap value of 0.000. Loyalty has a positive and significant effect on performance with an original sample value of 0.200 and ap value of 0.021. Work Motivation has a positive and significant effect on Work Discipline with an original sample value of 0.324 and ap value of 0.000. Work Motivation has a positive and insignificant effect on performance with an original sample value of 0.169 and ap value of 0.056. Loyalty has a positive and significant indirect effect on performance through work discipline with an original sample value of 0.316 and ap value of 0.000. Work Motivation has a positive and significant indirect effect on performance through Work Discipline with an original sample value of 0.171 and ap value of 0.001.